Dependence of the apparent bicarbonate space on initial plasma bicarbonate concentration and carbon dioxide tension in neonatal calves with diarrhea, acidemia, and metabolic acidosis. (15th January 2021) - Trefz, Florian M.; Lorenz, Ingrid; Constable, Peter D.
Abstract: Background: Marked strong ion (metabolic) acidosis in neonatal diarrheic calves usually is corrected by IV administration of NaHCO3 . The distribution space for IV‐administered bicarbonate, called the apparent bicarbonate space (ABS), appears to depend on initial plasma bicarbonate concentration ( c HCO3 ) and varies considerably in calves. Objective: To determine whether ABS was associated with initial plasma c HCO3 and other acid‐base variables. Animals: Twenty‐five neonatal diarrheic calves with acidemia and metabolic acidosis. Methods: Prospective observational study using a convenience sample. Calves received NaHCO3 (10 mmol/kg) and glucose (1.4 mmol/kg) IV in a crystalloid solution at 25 mL/kg over 60 minutes. The ABS (L/kg) was calculated at 4 time points over 2 hours after the end of the infusion. The relationship between ABS and initial acid‐base variables was characterized using nonlinear, linear, and stepwise regression. Results: The median value for ABS calculated from the initial plasma c HCO3 increased from 0.53 L/kg (range, 0.40‐0.79) at the end of IV infusion to 0.96 L/kg (range, 0.54‐1.23) 120 minutes later. Data obtained at the end of infusion provided the best fit to initial plasma c HCO3 and jugular venous blood Pco2, such that: ABS = 0.41 + 1.06/ c HCO3 and ABS = 0.87‐0.0082 × Pco2 . Conclusions and Clinical Importance: The observed median value for ABS of 0.53 L/kg in our study was similar to the empirically used value of 0.6. However, ABS values varied widely and were increased in calves with severe metabolic acidosis. We therefore recommend calculating ABS using the initial plasma c HCO3 or venous blood Pco2, if respective measurements are available.